Dietary patterns and breast cancer risk, prognosis, and quality of life: A systematic review - Bu, Yuan; Qu, Junchao; Ji, Siqi; Zhou, Jingxin; Xue, Mengxin; Qu, Jiling; Sun, Huiping; Liu, Yongbing (Frontiers in Nutrition, 2023)
Background: Statistics indicate that the morbidity of breast cancer is increasing globally, and its (overall figures) incidence has now surpassed that of lung cancer for the first time. The relation between a whole dietary pattern, rather than of a single food or nutrient, and breast cancer (BC) should be examined for findings to capture the complexities of diet and the potential for synergism between dietary components. Hence, the effects of dietary patterns on breast cancer have recently attracted increasing attention. Objective: To systematically review the effects of dietary patterns on breast cancer risk, prognosis, and quality of life in survivors. Methods: This systematic review was conducted following PRISMA guidelines and was registered in PROSPERO. Data from Ovid, China Biomedical Literature Database, Wanfang Data Knowledge Service Platform, CNKI, PubMed, Weipu, The Cochrane Library, Duxiu Data, ProQuest, Embase, Web of Science, and Scopus Database were retrieved and evaluated. Results: A total of 47 studies that investigated the association between eating patterns and breast cancer were identified. Ten studies evaluated the effect of the model on treatment outcome and prognosis of breast cancer and two cross-sectional studies examined the influence of dietary patterns on quality of life. The resulting favorable dietary patterns were shown to regulate metabolic biomarkers, antioxidants, anti-inflammatory agents, and protective genes, and inhibit cell proliferation and invasion. Conclusion: Numerous studies have examined the effects of healthy eating, plant-based, anti-inflammation, low-fat, and other favorable dietary patterns in relation to breast cancer. However, few studies reported significant associations and the studies had limitations, suggesting that the current findings should be interpreted with caution. Registration: PROSPERO Registration number CRD42022350171. Keywords: Dietary patterns; Breast cancer; Breast cancer risk; Prognosis; Quality of life.